An integrated microfluidic 3D tumor system for parallel and high-throughput chemotherapy evaluation. Issue 20 (7th September 2020) - Liu, Wenming; Liu, Dan; Hu, Rui; Huang, Zhongchao; Sun, Meilin; Han, Kai
Abstract : We present a multifunction-integrated microfluidic 3D tumor array platform for high-throughput and multi-parallel chemotherapy evaluation with microscale control. Abstract : The development of a microplatform with multifunctional integration allowing the dynamic and high-throughput exploration of three-dimensional (3D) cultures is promising for biomedical research. Here, we introduce an integrated microfluidic 3D tumor system with pneumatic manipulation and chemical gradient generation to investigate anticancer therapy in a parallel, controllable, dynamic, and high-throughput manner. The stability of the microfluidic system to realize precise and long-term chemical gradient production was developed. Serial manipulations including active cell trapping, array-like tumor self-assembly and formation, reliable gradient generation, parallel multi-concentration drug stimulation, and real-time tumor analysis were achieved in a single microfluidic device. The microfluidic platform was demonstrated to be stable for high-throughput cell trapping and 3D tumor formation with uniform quantities. On-chip analysis of phenotypic tumor responses to diverse chemotherapies with different concentrations can be conducted in this device. The microfluidic advancement holds great potential for applications in the development of high-performance and multi-functional biomimetic tumor systems and in the fields of cancer research and pharmaceutical development.